Xác định điều kiện môi trường địa chất thích hợp cho sự bảo tồn và phát triển của sá sùng ở ven biển đảo Quan Lạn - Quảng Ninh - Hà, Nguyễn Thị Thu; Ngợi, Chu Văn; Lan, Nguyễn Thanh (VNU Journal of Science: Natural Sciences and Technology; Vol 20 No 4, 2004)
Sasung (Phaseolosoma esculenta) is a special kind of seafood in high value and has been prefered in China market. However researches on the growing condition of Sasung is still few. In order to reflect clearly the living characteristics of Sasung, the authors carried out researching biological characteristics of Sasung and environmental criteria of water and surface sediment in surveyed area of Sasung located in Quanlan islands, Vandon district, Quangninh province. The results of this research can be applied effectively for rearing Sasung.